Epidemiology, Pathophysiology, and Management of Coronary Artery Disease in the Elderly - Fadah, Kahtan; Hechanova, Aimee; Mukherjee, Debabrata (International Journal of Angiology, 2022)
Elderly patients over the age of ≥ 75 years are especially susceptible to coronary artery disease (CAD) as age is an important nonmodifiable risk factors for atherosclerosis and a predictor of poorer outcomes. In fact, CAD is a major cause of mortality and morbidity in this population. Due to concerns of functional frailty, comorbidities, and patient preference of conservative to no treatment have played a role in reducing the interest in pursuing prospective studies in this high-risk group. In this review, we provide an overview of the epidemiology, pathophysiology, and management of CAD in older adults.
Keywords: elderly; aging; coronary artery disease; atherosclerosis; frailty; revascularization